2022
DOI: 10.1007/s12072-022-10346-3
|View full text |Cite
|
Sign up to set email alerts
|

The immune microenvironment features and response to immunotherapy in EBV-associated lymphoepithelioma-like cholangiocarcinoma

Abstract: Background & Aims Limited data are available for tumor immune microenvironment (TIME) in Epstein-Barr virus (EBV)-associated lymphoepithelioma-like cholangiocarcinoma (EBV-LELCC), a rare subtype of intrahepatic cholangiocarcinoma (IHCC). We aimed to investigate TIME features in EBV-LELCC and the correlation between the components of TIME and the clinical outcomes.Methods Tumor tissues from Five EBV-LELCC cases con rmed through EBER in situ hybridization and ve stage-matched conventional IHCC (non-EBV IHCC) cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…The high ICD subgroup is associated with a better prognosis and higher levels of immune cell infiltration than the low ICD subgroup. Some studies have reported better efficacy of tumor-applied immunosuppression when suppressor receptors are highly expressed ( 28 ), which is consistent with our findings. Among the different subtypes of ICD, the frequency of mutations was slightly higher in the high ICD subtype than in the low subtype group.…”
Section: Discussionsupporting
confidence: 93%
“…The high ICD subgroup is associated with a better prognosis and higher levels of immune cell infiltration than the low ICD subgroup. Some studies have reported better efficacy of tumor-applied immunosuppression when suppressor receptors are highly expressed ( 28 ), which is consistent with our findings. Among the different subtypes of ICD, the frequency of mutations was slightly higher in the high ICD subtype than in the low subtype group.…”
Section: Discussionsupporting
confidence: 93%
“…Various cells with viral infections are capable of producing type I interferon response [ 44 , 45 ], which attracts abundant immune cell infiltration. Not surprisingly, EBV-related tumors are characterized as immune “hot” tumors with a strong adaptive immune response [ 46 , 47 , 48 ]. However, increasing immune cell infiltration in tumors by artificial EBV infections would not be ethical.…”
Section: Discussionmentioning
confidence: 99%
“…Rokutan et al [43] observed MUC6 mutating in 20% of gastric dysplasia/intraepithelial neoplasia samples. Moreover, MUC6 mutations were found in Epstein-Barr virus (EBV)associated lymphoepithelioma-like cholangiocarcinoma [44], and directly associated with thyroid cancer [45]. On the other hand, the mutation status of MUC6 and three other genes (ATR, ERBB3 and KDR) was obtained as a marker for the recurrence of non-small-cell lung cancer (NSCLC) patients [46].…”
Section: Discussionmentioning
confidence: 99%